Strategies and Challenges in Biodiversity Conservation: Solutions for Ecosystem Sustainability - Ngadi Permana; Eddy Iskandar (LPPM STIE Kasih Bangsa, 2025)
This study aims to identify challenges and solutions in biodiversity conservation through a qualitative literature review. With increasing threats to biodiversity due to human activities, such as habitat loss, climate change, and pollution, conservation efforts are becoming increasingly important. Through a literature analysis covering a wide range of sources, this study found that the challenges faced are complex and often interconnected. Proposed solutions include empowering local communities, using innovative technologies, and improving policies and cross-sector collaboration. This study also shows the importance of evidence-based data to inform conservation policies and practices. While much effort has been made, the challenges require a more integrated and collaborative approach. The conclusions of this study emphasize the need for continued investment in research and development to protect biodiversity and ensure its sustainability for future generations.